COMPETENT APPROACH IN THE PROCESS OF TEACHER’S PROFESSIONAL PREPARATION - Кubitska Маria D. (Educological discourse, 2016)
The article deals with the meaning of the concept «competent approach» in modern science. The author uses the experience of home and foreign researchers. Different meanings of the term «competence» are summarized; the list of main competencies necessary for a future teacher is given. The concept professional competence is determined and proved.